2019
DOI: 10.1007/s42421-019-00008-6
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Activity–Travel Behavior Time Series using Topological Data Analysis

Abstract: Over the last few years, traffic data has been exploding and the transportation discipline has entered the era of big data. It brings out new opportunities for doing data-driven analysis, but it also challenges traditional analytic methods. This paper proposes a new Divide and Combine based approach to do K-means clustering on activity-travel behavior time series using features that are derived using tools in Time Series Analysis and Topological Data Analysis. Our approach facilitates a case study, where each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…With recent advances in location and communication technologies (e.g., GPS, smart phones), probe vehicle data are now widely available and accessible. Because these data are collected from the traffic stream, they contain rich information on how transportation systems are used as well as their traffic conditions ( 4 ). A recent NCHRP Synthesis study found that at least 20 state DOTs have acquired and used probe vehicle speed/travel time data from third-party vendors ( 5 ).…”
mentioning
confidence: 99%
“…With recent advances in location and communication technologies (e.g., GPS, smart phones), probe vehicle data are now widely available and accessible. Because these data are collected from the traffic stream, they contain rich information on how transportation systems are used as well as their traffic conditions ( 4 ). A recent NCHRP Synthesis study found that at least 20 state DOTs have acquired and used probe vehicle speed/travel time data from third-party vendors ( 5 ).…”
mentioning
confidence: 99%
“…Persistent homology on functions can be used to construct features via persistence landscapes that enable us to carry out unsupervised or supervised learning of time series. In the literature, different representations of time series have been used, such as the weighted Fourier transform in Wang et al (2018) or the WFT in Chen et al (2019). We describe these situations in the following sections.…”
Section: Feature Construction Using Tdamentioning
confidence: 99%
“…In Figure 11, the first column shows categorical time series on activity‐travel behavior of two randomly chosen adults from the National Household Travel Survey (Chen et al, 2019). The length of each time series is T = 1440, corresponding to the number of minutes in a day.…”
Section: Feature Construction Using Tdamentioning
confidence: 99%
See 1 more Smart Citation
“…Topological data analysis has been used previously in the context of traffic data: [19] uses TDA as a model for tracking vehicles and [20] uses TDA to understand individual travel behaviors. TDA has also been used previously for anomaly detection in [21,22].…”
Section: Survey Of Literaturementioning
confidence: 99%